10+0.07(15x)+9x=15x

Simple and best practice solution for 10+0.07(15x)+9x=15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+0.07(15x)+9x=15x equation:


Simplifying
10 + 0.07(15x) + 9x = 15x

Remove parenthesis around (15x)
10 + 0.07 * 15x + 9x = 15x

Multiply 0.07 * 15
10 + 1.05x + 9x = 15x

Combine like terms: 1.05x + 9x = 10.05x
10 + 10.05x = 15x

Solving
10 + 10.05x = 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
10 + 10.05x + -15x = 15x + -15x

Combine like terms: 10.05x + -15x = -4.95x
10 + -4.95x = 15x + -15x

Combine like terms: 15x + -15x = 0
10 + -4.95x = 0

Add '-10' to each side of the equation.
10 + -10 + -4.95x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -4.95x = 0 + -10
-4.95x = 0 + -10

Combine like terms: 0 + -10 = -10
-4.95x = -10

Divide each side by '-4.95'.
x = 2.02020202

Simplifying
x = 2.02020202

See similar equations:

| 3+n+5= | | 8x-15=3x+11 | | 3+5x=2x+3 | | 10x+17=-143+2x | | 16-4n=-n | | 6n+4=-18n | | y+7=-14 | | 4x-12=12-6x | | 3x+10=9x-2 | | (2x-3)/(5x-1) | | 43-2=13x-83 | | 2x+54=-21+x | | -28=4/5d | | -36x^2+4=0 | | 14x-28=24-12x | | n+14=11 | | 3(y+7)(-y-2)=0 | | 10+7n=5-6 | | 14/z=9-z | | 4x+9=180 | | 8x-66=36+2x | | x+-9=15 | | x^2+3x+756=0 | | 64=8y | | Cos(2x)+sin(2x)=0 | | 3.3+3.83= | | An=2A | | (8-v)(2v+5)=0 | | 21+c=30 | | r^2+42r=0 | | 380=2(w+1)+2(w+20) | | 4x+2(16/5)=8 |

Equations solver categories